Meat molecular detection: sensitivity of polymerase chain reaction-restriction fragment length polymorphism in species differentiation of meat from animal origin - Ong, Sang Bing; Mat Issa @ Zakaria, Zuraini; Gunsalam, Jurin Wolmon; Cheah, Yoke Kqueen; Robin, Tunung; Chai, Lay Ching; Yuli, Haryani; Mohamad Ghazali, Farinazleen; Radu, Son (Universiti Putra Malaysia Press, 2007)
Three restriction enzymes were used in Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) using the mitochondrial cytochrome b region to establish a differential diagnosis which detect and discriminate between three meat species: pork, cow and chicken. DNA was extracted from samples containing meat of a single animal such as raw pork (Sus scrofa domesticus), chicken (Gallus gallus) and cow (Bos taurus) as well as mixed samples of two species of animals in different ratios. The amplified 359 base pairs (bp) portion of the mitochondrial cyt b gene from pure or mixed samples in different ratios was cut using three different restriction enzymes resulting in species specific restriction fragment length polymorphism (RFLP). This technique proved to be extremely reliable in detecting the presence of low levels of target DNA obtained from a 0.25 mg component in a particular mixed meat sample. This revealed the cyt b region as highly conserved and consequently a good molecular marker for diagnostic studies. Thus, this technique can be applied to food authentication for the identification of different species of animals in food products.